EASIX for Prediction of Outcome in Hospitalized SARS-CoV-2 Infected Patients - Luft, Thomas; Wendtner, Clemens-Martin; Kosely, Florentina; Radujkovic, Aleksandar; Benner, Axel; Korell, Felix; Kihm, Lars; Bauer, Matthias F.; Dreger, Peter; Merle, Uta (Frontiers in Immunology, 2021)
Background: The coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and has evoked a pandemic that challenges public health-care systems worldwide. Endothelial cell dysfunction plays a key role in pathophysiology, and simple prognosticators may help to optimize allocation of limited resources. Endothelial activation and stress index (EASIX) is a validated predictor of endothelial complications and outcome after allogeneic stem cell transplantation. Aim of this study was to test if EASIX could predict life-threatening complications in patients with COVID-19. Methods: SARS-CoV-2-positive, hospitalized patients were enrolled onto a prospective non-interventional register study (n=100). Biomarkers were assessed at hospital admission. Primary endpoint was severe course of disease (mechanical ventilation and/or death, V/D). Results were validated in 126 patients treated in two independent institutions. Results: EASIX at admission was a strong predictor of severe course of the disease (odds ratio for a two-fold change 4.2, 95%CI 1.9-9.3, p<0.001), time to V/D (hazard ratio (HR) for a two-fold change 2.2, 95%CI 1.6-3.0, p<0.001) as well as survival (HR for a two-fold change 2.1, 95%CI 1.4-3.1, p<0.001). The effect was retained in multivariable analysis adjusting for age, gender, and comorbidities and could be validated in the independent cohort. EASIX correlated with increased suppressor of tumorigenicity-2, soluble thrombomodulin, and angiopoietin-2 at admission. Conclusion: EASIX is a validated predictor of COVID19 outcome and an easy-to-access tool to segregate patients in need for intensive surveillance.